2014
DOI: 10.3390/rs6010521
|View full text |Cite
|
Sign up to set email alerts
|

Peat Mapping Associations of Airborne Radiometric Survey Data

Abstract: This study considers recent airborne radiometric (gamma ray) survey data, obtained at high-resolution, across various regions of the UK. The datasets all display a very evident attenuation of signal in association with peat, and intra-peat variations are observed. The geophysical response variations are examined in detail using example data sets across lowland areas (raised bogs, meres, fens and afforested peat) and upland areas of blanket bog, together with associated wetland zones. The radiometric data do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…The threshold of 800 cps is used since it largely outlines the extent of the Blanket Bog as defined in Figure 2a. As is usual in radiometric peat studies (Beamish, 2014), intra-peat variations are observed and the lowest interval (e.g. < 100 cps) would imply 100% saturation.…”
Section: The Case-study Area: Soilmentioning
confidence: 93%
See 1 more Smart Citation
“…The threshold of 800 cps is used since it largely outlines the extent of the Blanket Bog as defined in Figure 2a. As is usual in radiometric peat studies (Beamish, 2014), intra-peat variations are observed and the lowest interval (e.g. < 100 cps) would imply 100% saturation.…”
Section: The Case-study Area: Soilmentioning
confidence: 93%
“…Peat soils, in particular, produce readily identifiable attenuation zones. The radiometric data can therefore be used for peat mapping and hence assessments of the lateral extent of the carbon store (Beamish, 2014). Although the bedrock provides a specific radiogenic level with associated radiochemical attributes, attenuation of the signal level is controlled by soil moisture content in conjunction with the density and porosity of the soil cover.…”
Section: Introductionmentioning
confidence: 99%
“…Each survey provides a spatially-dense radioelement mapping with derived dose rates. An example is first provided using data from the latest (2013) TellusSW survey Beamish et al, 2014). Figure 3a shows a radioelement ternary image formed from the three %K, eTh and eU contributions.…”
Section: Resultsmentioning
confidence: 99%
“…In the limiting case of wet peat attenuation levels increase by >50% over their 'dry' equivalents. The behaviour is so distinctive that dose-rate estimates can be used to map peat areas across the UK (Beamish, 2014).…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation